2018
DOI: 10.1016/j.bpj.2018.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Multivalent Binding of a Ligand-Coated Particle: Role of Shape, Size, and Ligand Heterogeneity

Abstract: We utilize a multiscale modeling framework to study the effect of shape, size, and ligand composition on the efficacy of binding of a ligand-coated particle to a substrate functionalized with the target receptors. First, we show how molecular dynamics along with steered molecular dynamics calculations can be used to accurately parameterize the molecular-binding free energy and the effective spring constant for a receptor-ligand pair. We demonstrate this for two ligands that bind to the αβ-domain of integrin. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 109 publications
(174 reference statements)
2
38
0
Order By: Relevance
“…While VHH density promoted specific attachment, the adhesin affinity and reaction rates ended up being a surprisingly weak regulator of attachment and detachment. This could be explained by the fact after engaging several adhesins of relatively high affinity, bacterial overall avidity rapidly predominates over the affinity of individual adhesins 35 . In contrast, we found that mechanical factors of the host environment strongly regulate each of the stages of adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…While VHH density promoted specific attachment, the adhesin affinity and reaction rates ended up being a surprisingly weak regulator of attachment and detachment. This could be explained by the fact after engaging several adhesins of relatively high affinity, bacterial overall avidity rapidly predominates over the affinity of individual adhesins 35 . In contrast, we found that mechanical factors of the host environment strongly regulate each of the stages of adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…∆ G is the free energy of pinning and k bell the stiffness of the pinning interaction. For the results presented here we take the interaction energy parameters that are comparable to intercellular adhesion molecule ICAM [44], given as ∆ G = 19 k B T and k bell = 60 k B T/a 0 , unless otherwise stated. To extend our model to include other adhesion molecules, we also study the effect of a range of pinning energy parameters.…”
Section: Model and Computational Methodsmentioning
confidence: 99%
“…An important aspect of MNPs is their bioconjugation by using a variety of surface functionalization molecules, which may help the peptide-NP conjugate to cross the multiple biological barriers they face and protect them from mechanisms of immune recognition and cellular clearance [135]. Based in the principle of multivalence, the unique interactions between peptide and NP surface provide an improved selectivity [147]. Depending on the NP shape, size and surface chemistry, the binding of a functionalized nanoparticle can promote or enhance specificity to target cells or cell surface molecules [37].…”
Section: Metal Nanoparticlesmentioning
confidence: 99%